TECHNOLOGY FORECASTING USING THEORY OF INVENTIVE PROBLEM SOLVING: A CASE STUDY OF AUTOMOTIVE HEADLAMP SYSTEM - Zulhasni Abdul Rahim; Nooh Abu Bakar (PERINTIS eJournal, 2021)
This paper deals with the drawbacks of the current application of technology forecasting by introducing a new methodology, the Theory of Inventive Problem Solving, or commonly known as TRIZ. After explaining some critical issues and constraints of technology forecasting, a proposed framework that adopted the TRIZ methodology was presented to address the highlighted issues. Then, a case study was presented on the technology forecast of an innovation of automotive component using the proposed framework. This paper helps practitioners to understand the trends, aligned with the industry value, and push forward towards the goal of products design improvement and innovation management.